New commercial polyurethane synthesized with biopolyol obtained from canola oil: Optimization, characterization, and thermophysical properties - Aydogmus, Ercan; Kamisli, Fethi (Elsevier, 2022)
In this study, the production of polyurethanes from biopolyol obtained from canola oil has been investigated. Canola oil-based biopolyol was obtained by applying processes of epoxidation, hydroxylation, neutralization, and purification. The parameters such as the temperature, humidity, raw material, filler, catalyst, mixing speed, and pressure were optimized for the maximum yield. According to Taguchi optimization, to obtain biopolyol with maximum efficiency, approximately 75 g of hydrogen peroxide, and 76 g of methyl alcohol were added to 100 g of canola oil, and PID reactor system was worked for 6 h at 329 K. For the polyurethane synthesized from biopolyol, the approximate hydroxyl number was determined as 95 g KOH/g biopolyol, the amount of toluene diizosiyanat is 56 g, the amount of triethylene diamine is 0.2 g, the amount of stannous octoate is 0.25 g, and melamine is 11 g. The results of the experiments carried out in real conditions with Taguchi optimization data have been evaluated with physical and chemical tests. The pores in the polyurethane produced with polyols having low hydroxyl numbers are smaller and less while the polyols having high hydroxyl numbers used in the polyurethane production increase fragility and decrease mechanical strength. The effect of the particle size of the filler on the thermal conductivity has been also evaluated. It has been observed that the thermal conductivity of the polyurethane increased as the particle diameter of the used filler raised. Also, the rheological properties of canola oil and polyols obtained from canola oil were acquired at different values of temperatures.(c) 2022 Elsevier B.V. All rights reserved.
Keywords: Biopolyol; Canola oil; Optimization; Polyurethane; Thermophysical properties